An Approach to ICT Professionals' Skills Assessment based on European e-Competence Framework - Sokol, V.; Tkachuk, M.; Godlevskiy, M.; Bilova, M.; Studenikin, D. (My University, 2020)
The main aim of this research is to increase project effectiveness in the ICT domain. In order to achieve this goal, it was decided to focus on a process of team formation, since a strong team is undoubtedly one of the most significant components of a successful project. To build a stronger and potentially more effective team from a wide range of candidates with different skills and knowledge, it is vital to determine the most eligible ones. Therefore, it is necessary to assess available candidates and to make this process effective, it has to be formalized and then optimized. To perform a fairly objective assessment of a candidate for a role in a project an approach using a comparator identification method is proposed to increase the effectiveness of the whole process. The European e-Competence Framework and ICT Professionals’ Role Profiles documents are used to support this approach, and the appropriate software tool is designed to implement its main functionality.
Keywords: european e-competence framework; ICT professionals' role profiles; competence; role eligibility; assessment; software tool